2015
DOI: 10.1039/c4ee03389b
|View full text |Cite
|
Sign up to set email alerts
|

Spinel compounds as multivalent battery cathodes: a systematic evaluation based on ab initio calculations

Abstract: contributed equally to this work. AbstractBatteries that shuttle multi-valent ions such as Mg 2+ and Ca 2+ ions are promising candidates for achieving higher energy density than available with current Li-ion technology. Finding electrode materials that reversibly store and release these multi-valent cations is considered a major challenge for enabling such multi-valent battery technology. In this paper, we use recent advances in high-throughput firstprinciples calculations to systematically evaluate the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
647
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(693 citation statements)
references
References 73 publications
44
647
2
Order By: Relevance
“…The best candidate seems to be spinel MnO 2 , which has a barrier ∼ 650 meV. 48 Consistent with Liu et al's report, Kim et al reported the observation of reversible Mg intercalation into spinel-MnO 2 using aqueous Mg(NO 3 ) 2 eletrolyte (1 M) and Pt as the counter electrode. 49 The discharge delivered a capacity of 190 mAh/g.…”
Section: Oxide Cathodessupporting
confidence: 71%
See 1 more Smart Citation
“…The best candidate seems to be spinel MnO 2 , which has a barrier ∼ 650 meV. 48 Consistent with Liu et al's report, Kim et al reported the observation of reversible Mg intercalation into spinel-MnO 2 using aqueous Mg(NO 3 ) 2 eletrolyte (1 M) and Pt as the counter electrode. 49 The discharge delivered a capacity of 190 mAh/g.…”
Section: Oxide Cathodessupporting
confidence: 71%
“…48 All these compounds exhibit lower voltage than that of Li analogues. It is mainly a result of the high redox potential of Mg/Mg 2+ .…”
Section: Oxide Cathodesmentioning
confidence: 99%
“…Multivalent intercalation cathodes can exhibit very high energy density compared to their Li-ion counterparts, creating the materials innovation challenge of identifying host structures with sufficient ionic mobility. Systematically searching through redox-active cations and mobile multivalent species, Liu et al 69,70 predicted reasonable overall performance for Mg and Ca in the Mn oxide spinel structure ( Fig. 3), as well as in the Cr, Ti, and Mn sulfide spinels.…”
Section: Energy Conversion: Thermoelectricsmentioning
confidence: 99%
“…4 This sluggish diffusion of Mg 2+ compared to Li + is presumed to be due to the strong Mg inter-actions with the anions and the cations of the hosts, giving rise to a low Mg intercalation level and a large difference between the charge and discharge potentials. The reasons behind the sluggish diffusion of Mg in spinel materials were recently further studied by Ceder et al and Persson et al 25,26 In order to improve this issue, reducing the particle size of the electrode material has been widely used, which significantly shortens the diffusion lengths of ions and electrons within the particles, resulting in more efficient and rapid access of the active cations. 27 Moreover, increased surface area ensures better contact between the electrolyte and active material.…”
Section: Introductionmentioning
confidence: 99%